An In vitro Approach to Optimize Levels of Moringa oleifera Meal Incorporation in Total Mixed Ration for Crossbred Heifer Calves - P. M, Lunagariya; A. N., Sherasiya; K. K., Sorathiya; J. H., Patel; P. R., Pandya (International Journal of Bio-resource and Stress Management, 2022)
An in vitro experimentation outside living animals to evaluate feed/fodders on digestibility and gas production is cheap, easy and having more control condition as compared to an in vivo evaluation on livestock which is costly and time-consuming event. The incorporation of Moringa oleifera meals @ 2.5– 22.5% with increment of 2.5% in total mixed ration-TMR replacing concentrate mixture (50%) was assessed on in vitro digestibility, total gas production (TGP) and metabolizable energy (ME) content for growing crossbred heifer calves. The roughage part (50%) of TMR was hybrid napier (15%) and ground nut straw (35%). All these ingredients were oven dried for twenty four hour at 70°C and finely ground in hammer mill using 1 mm sieve. 500 mg of each TMR were incubated at 39±1°C for 48 hours in triplicate along with blank without TMR. The results of experiment revealed that incorporation of Moringa oleifera meal @ 5.0% with increment levels of 2.5% and higher levels up to 22.5% to replace high protein concentrate mixture (50%) in total mixed ration containing 50% roughage (15% hybrid napier and 35% ground nut straw) has improved (p<0.05) in vitro dry matter digestibility (60.879±0.251 to 64.678±0.679%), in vitro gas production (81.000±9.018 to 95.667±1.764 ml/500 mg TMR) and ME content (2.356±0.068 to 3.223±0.057 Mcal ME kg-1 TMR) of total mixed ration. The levels 5% and above up to 22.5% with increment of 2.5% level in total mixed ration replacing concentrate mixture was found suitable for in vivo growth study of crossbred heifer calves.